Preparation method of conductive fly ash ceramsite, concrete and preparation method thereof
By using conductive ceramics and a small amount of carbon fibers prepared by high-speed iron fly ash, the problem of non-conductive and discontinuity of aggregates in existing conductive concrete is solved, and the conductive performance is improved and the mechanical properties are maintained.
Patent Information
- Application Number
- CN202411976966.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The aggregate in existing conductive concrete is not conductive, and the conductivity between conductive materials is discontinuous, resulting in unsatisfactory conductive effect. Too much conductive material will affect the mechanical properties of the concrete.
High-speed iron fly ash is used to prepare clay particles with conductive properties as conductive aggregates, and combined with a small amount of carbon fiber in the cement slurry, the conductive properties are improved through the reduction-magnetic separation-reduction sintering process, while ensuring the mechanical properties of concrete.
The conductive properties of concrete are significantly improved, while maintaining good mechanical properties. Through the full utilization of resources, the efficient preparation and application of conductive ceramics are achieved.
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, and in particular to a method for preparing conductive fly ash ceramsite, concrete and a preparation method thereof. Background Art
[0002] Conventional conductive concrete is made by adding non-metallic conductive materials such as carbon fiber, carbon nanotubes, graphite, carbon black, or metallic conductive materials such as steel fiber and steel slag into cement paste. However, the volume proportion of cement paste in concrete is limited, and the aggregates that account for a large volume proportion in concrete are not conductive, resulting in unsatisfactory conductivity of concrete. If the amount of conductive materials added to cement paste is increased, the mechanical properties of concrete will be affected. Prior art, such as the patent document with publication number CN112521076A, discloses a high-strength conductive concrete with large slump of iron tailings and a preparation method thereof, and discloses the preparation of conductive concrete using iron ore waste rock as coarse aggregate, iron tailings sand, and iron ore concentrate as fine aggregate. Summary of the invention
[0003] In order to solve the problems in the existing conductive concrete that the aggregates occupying a relatively large volume are not conductive, the conductivity between the conductive materials is discontinuous, the conductive effect of the added conductive materials is not ideal, and the excessive addition affects the mechanical properties of the concrete, the present invention provides a method for preparing conductive fly ash ceramsite, concrete and a preparation method thereof, wherein ceramsite with conductive properties is prepared using high iron fly ash and is used as a conductive aggregate in concrete, and a small amount of carbon fiber is added to the cement paste, so that the conductive properties of the concrete can be improved and the mechanical properties of the concrete can be guaranteed.
[0004] The technical objectives of the present invention are achieved through the following technical solutions:
[0005] A method for preparing conductive fly ash ceramsite, the method comprising:
[0006] S1. placing high iron fly ash containing magnetite and hematite in a roasting furnace, and roasting at a roasting temperature of 800° C. for 30 min to obtain roasted fly ash A, wherein the roasted fly ash A contains magnetite;
[0007] S2, dispersing the calcined fly ash A in water to obtain a calcined fly ash solution B, separating the magnetic substance in the calcined fly ash solution B to obtain wet high magnetic fly ash C and low magnetic fly ash solution D;
[0008] S3, drying the wet high magnetic fly ash C to constant weight to obtain high magnetic fly ash; drying the low magnetic fly ash solution D to constant weight to obtain low magnetic fly ash;
[0009] S4, granulating the high magnetic fly ash to form fly ash ceramsite raw balls E;
[0010] S5, calcining the fly ash ceramsite raw balls E in a reducing atmosphere, including three stages:
[0011] In the first stage, the preheating temperature is 400°C and the preheating time is 30 minutes;
[0012] In the second stage, the calcination temperature was 1100°C and the sintering time was 20 min;
[0013] In the third stage, rapid cooling for 15 min, the temperature dropped to room temperature, and crude conductive fly ash ceramsite F was obtained;
[0014] S6. Screening the crude conductive fly ash ceramsite F to obtain conductive fly ash ceramsite and conductive fly ash ceramic sand, wherein the particle size of the conductive fly ash ceramsite is ≥5 mm and ≤20 mm, and the particle size of the conductive fly ash ceramic sand is ≥1.25 mm and <5 mm.
[0015] Furthermore, the Fe2O3 content in the high iron fly ash is 14% to 20%, the SiO2 content is 45% to 54%, the Al2O3 content is 25% to 30%, the Na2O content is 0.5% to 1%, the K2O content is 0.5% to 1%, the CaO content is 1% to 4%, the MgO content is 0.5% to 3%, and the residual carbon content is 4% to 6%.
[0016] Furthermore, the mass ratio of the calcined fly ash A to water is 1:9 to 1:4.
[0017] Furthermore, the content of Fe2O3 in the high magnetic fly ash is 45% to 60%, and the content of Fe2O3 in the low magnetic fly ash is 2% to 6%.
[0018] Furthermore, the apparent density of the conductive fly ash ceramsite is 2200-2500 kg / m 3 , the cylinder pressure strength is 8~12MPa.
[0019] Furthermore, the apparent density of the conductive fly ash ceramic sand is 2350-2600 kg / m 3 , the cylinder pressure strength is 9~12MPa.
[0020] Furthermore, in step S2, it includes:
[0021] Step S21, stirring the roasted fly ash solution B by a magnetic bar with a magnetic induction intensity of 1T, so that the magnetic substance in the roasted fly ash solution B is adsorbed on the surface of the magnetic bar, and the magnetic substance on the surface of the magnetic bar is collected for later use; repeating the above process until the surface of the magnetic bar with a magnetic induction intensity of 1T is no longer adsorbed with magnetic substances;
[0022] Step S22, stirring the roasted fly ash solution B after the treatment in the above step S21 by a magnetic bar with a magnetic induction intensity of 1.2T, so that the magnetic substance in the roasted fly ash solution B is adsorbed on the surface of the magnetic bar with a magnetic induction intensity of 1.2T, collecting the magnetic substance on the surface of the magnetic bar with a magnetic induction intensity of 1.2T for later use, and repeating the operation until the surface of the magnetic bar with a magnetic induction intensity of 1.2T is no longer adsorbed with magnetic substances;
[0023] Step S23, the collected magnetic substances are mixed to obtain wet high magnetic fly ash C, and the roasted fly ash solution B is processed in step S22 to obtain low magnetic fly ash solution D.
[0024] The present invention also provides a conductive concrete with integrated structure and function, which comprises, by mass ratio, 200-220 parts of cement, 60-70 parts of low magnetic fly ash, 90-100 parts of mineral powder, 880-930 parts of conductive fly ash ceramsite, 720-760 parts of conductive fly ash ceramic sand, 0.5-2 parts of carbon fiber, 4-6 parts of water reducing agent, and 165-170 parts of water, wherein the low magnetic fly ash, the conductive fly ash ceramsite and the conductive fly ash ceramic sand are prepared by the above-mentioned method for preparing the conductive fly ash ceramsite.
[0025] Furthermore, the carbon fiber is a polyacrylonitrile-based carbon fiber with a length of 5 to 8 mm, a diameter of 6 to 8 μm, and a density of 1.5 to 2 g / cm 3 , tensile strength is 4-8GPa, tensile modulus is 300-500GPa, and carbon content is >90%.
[0026] Furthermore, the water reducer is a high-performance polycarboxylate water reducer.
[0027] The present invention also provides a method for preparing structurally integrated conductive concrete, the method comprising:
[0028] S1. Take 880-930 parts of conductive fly ash ceramsite and 720-760 parts of conductive fly ash ceramic sand according to the mass ratio, soak them in water for 24 hours respectively, and weigh them to determine the water absorption of the conductive fly ash ceramsite and the conductive fly ash ceramic sand;
[0029] S2, taking 0.5-2 parts of carbon fiber and dispersing them ultrasonically in 40-60 parts of water for 30-60 minutes to obtain an ultrasonically dispersed carbon fiber mixed solution K for standby use;
[0030] S3, taking 200-220 parts of cement, 60-70 parts of low magnetic fly ash, 90-100 parts of mineral powder, 880-930 parts of pre-wetted conductive fly ash ceramsite and 720-760 parts of pre-wetted conductive fly ash ceramic sand, stirring and mixing them evenly to obtain dry material I;
[0031] S4, take 4 to 6 parts of water reducing agent, pour it into the remaining water and stir it evenly, then add it into the dry material I and mix and stir evenly to obtain slurry J;
[0032] S5. Add the ultrasonically dispersed carbon fiber mixture K into the slurry J, and stir evenly to obtain the structural and functional integrated conductive concrete.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The conductive fly ash ceramsite prepared by the preparation method of the conductive fly ash ceramsite of the present invention has high cylinder pressure strength and good electrical conductivity. Through the reduction-magnetic separation-reduction sintering process, the weakly magnetic hematite is reduced to the strongly magnetic magnetite through the residual carbon in the fly ash, and no additional reducing agent is required. The magnetic separation will screen out the high magnetic fly ash, and the high magnetic fly ash is sintered in a reducing atmosphere to form a single iron substance, thereby improving the electrical conductivity of the fly ash ceramsite;
[0035] In addition, substances such as Na20 and K2O in fly ash can play a fluxing role during the sintering process without the need to add additional flux.
[0036] 2. The low magnetic fly ash produced in the process of preparing conductive fly ash ceramsite and conductive fly ash ceramic sand can be used in the preparation of conductive concrete to achieve full utilization of resources;
[0037] Among them, most of the iron oxides are removed from the low-magnetic fly ash, the iron content is reduced, and the content of active silicon and aluminum substances is increased, thereby increasing the volcanic ash activity of the fly ash, which is beneficial to improving the strength of concrete when used in concrete.
[0038] 3. The present invention uses conductive fly ash ceramsite that occupies a relatively large volume of concrete as a conductive material, and cooperates with a small amount of carbon fiber in the cement paste to further improve the conductive performance of the concrete. A small amount of carbon fiber is used to reduce the short circuit between the ceramsite, and a small amount of carbon fiber addition will not have a negative impact on the mechanical properties of the concrete. The conductive performance of the concrete is significantly improved through the synergy of aggregate and slurry, the synergy of metal conductive materials and non-metallic conductive materials, and the synergy of fiber materials and granular materials.
[0039] 4. The present invention uses a combination of ultrasonic dispersion and dispersant to evenly disperse carbon fibers in cement paste. The added polycarboxylic acid water reducer plays the role of a common water reducer on the one hand, and on the other hand, because it is an anionic surfactant, it can also promote the dispersion of carbon fibers.
[0040] 5. In the process of magnetic separation in the present invention, a magnetic rod with a magnetic induction intensity of 1T is first used for stirring to adsorb strong magnetic substances with high adsorption efficiency; then a magnetic rod with a magnetic induction intensity of 1.2T is used for stirring to adsorb weak magnetic substances, thereby improving the adsorption amount and adsorption effect. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below in conjunction with specific embodiments:
[0042] Example 1
[0043] A method for preparing conductive fly ash ceramsite, comprising:
[0044] S1. Placing high-iron fly ash containing magnetite and hematite in a roasting furnace, and roasting at a roasting temperature of 800°C for 30 minutes to obtain roasted fly ash A, wherein the roasted fly ash A contains magnetite; the high-iron fly ash has a Fe2O3 content of 14% to 20%, a SiO2 content of 45% to 54%, an Al2O3 content of 25% to 30%, a Na2O content of 0.5% to 1%, a K2O content of 0.5% to 1%, a CaO content of 1% to 4%, a MgO content of 0.5% to 3%, and a residual carbon content of 4% to 6%.
[0045] At this stage, hematite undergoes a reduction reaction at high temperature, and the reaction process is as follows:
[0046] 2C+O2=2CO
[0047] 3Fe2O3+CO=2Fe3O4+CO2
[0048] S2. Disperse calcined fly ash A in water, wherein the mass ratio of calcined fly ash A to water is 1:9 to 1:4, and in this embodiment, the mass ratio of calcined fly ash to water is 1:5, to obtain calcined fly ash solution B, separate the magnetic substance in the calcined fly ash solution B, and obtain wet high magnetic fly ash C and low magnetic fly ash solution D, wherein the main component of the magnetic substance is Fe3O4.
[0049] More specifically, the process is as follows:
[0050] Step S21, stirring the roasted fly ash solution B by a magnetic bar with a magnetic induction intensity of 1T, so that the magnetic substance in the roasted fly ash solution B is adsorbed on the surface of the magnetic bar, and the magnetic substance on the surface of the magnetic bar is collected for later use; repeating the above process until the surface of the magnetic bar with a magnetic induction intensity of 1T is no longer adsorbed with magnetic substances;
[0051] Step S22, stirring the roasted fly ash solution B after the treatment in the above step S21 by a magnetic bar with a magnetic induction intensity of 1.2T, so that the magnetic substance in the roasted fly ash solution B is adsorbed on the surface of the magnetic bar with a magnetic induction intensity of 1.2T, collecting the magnetic substance on the surface of the magnetic bar with a magnetic induction intensity of 1.2T for later use, and repeating the operation until the surface of the magnetic bar with a magnetic induction intensity of 1.2T is no longer adsorbed with magnetic substances;
[0052] Step S23, the collected magnetic substances are mixed to obtain wet high magnetic fly ash C, and the roasted fly ash solution B is processed in step S22 to obtain low magnetic fly ash solution D.
[0053] S3. Dry the wet high magnetic fly ash C to constant weight to obtain high magnetic fly ash; dry the low magnetic fly ash solution D to constant weight to obtain low magnetic fly ash, wherein the Fe2O3 content in the high magnetic fly ash is 45% to 60%, and the Fe2O3 content in the low magnetic fly ash is 2% to 6%.
[0054] When drying, it is dried in an oven at a drying temperature of 60°C.
[0055] S4, granulating the high magnetic fly ash to form fly ash ceramsite raw balls E, the specific operation is as follows:
[0056] During pelletizing, the high magnetic fly ash is placed on the disc of a disc ball making machine, and the disc is rotated horizontally while water is sprinkled until the high magnetic fly ash is rolled into a ball on the disc. After drying, fly ash ceramsite raw balls E are obtained.
[0057] S5, calcining the fly ash ceramsite raw balls E in a reducing atmosphere, including three stages:
[0058] In the first stage, the preheating temperature is 400°C and the preheating time is 30 minutes;
[0059] In the second stage, the calcination temperature was 1100°C and the sintering time was 20 min;
[0060] In the third stage, rapid cooling for 15 minutes, the temperature drops to room temperature, which is usually 20-25°C, to obtain crude conductive fly ash ceramsite F;
[0061] In the above process, magnetite is sintered in a reducing atmosphere to form iron. The main reaction process is as follows:
[0062] Fe3O4+4CO=3Fe+4CO2
[0063] S6. Screening the crude conductive fly ash ceramsite F to obtain conductive fly ash ceramsite and conductive fly ash ceramic sand, wherein the particle size of the conductive fly ash ceramsite is ≥5 mm and ≤20 mm, and the particle size of the conductive fly ash ceramic sand is ≥1.25 mm and <5 mm.
[0064] More specifically, the apparent density of conductive fly ash ceramsite is 2200-2500 kg / m 3 , cylinder pressure strength is 8-12MPa; the apparent density of conductive fly ash ceramic sand is 2350-2600kg / m 3 , the cylinder pressure strength is 9~12MPa.
[0065] Example 2
[0066] A conductive concrete with integrated structure and function, comprising, by mass ratio: 215 parts of cement, 62 parts of low magnetic fly ash, 93 parts of mineral powder, 910 parts of conductive fly ash ceramsite, 745 parts of conductive fly ash ceramic sand, 5 parts of high performance polycarboxylic acid water reducer, 1 part of carbon fiber, 165 parts of water, the low magnetic fly ash, conductive fly ash ceramsite and conductive fly ash ceramic sand are prepared by the method of the above embodiment 1. The carbon fiber is polyacrylonitrile-based carbon fiber, with a length of 5 to 8 mm, a diameter of 6 to 8 μm, and a density of 1.5 to 2 g / cm 3 , tensile strength is 4-8GPa, tensile modulus is 300-500GPa, and carbon content is >90%.
[0067] When preparing the above concrete, the following steps are included:
[0068] S1. Take 910 parts of conductive fly ash ceramsite and 745 parts of conductive fly ash sand in proportion by mass and soak them in water for 24 hours respectively, and weigh them to determine the water absorption of the conductive fly ash ceramsite and the conductive fly ash sand;
[0069] S2, taking 1 part of carbon fiber and dispersing it ultrasonically in 50 parts of water for 30 minutes to obtain an ultrasonically dispersed carbon fiber mixed solution K for standby use;
[0070] S3, taking 215 parts of cement, 62 parts of low magnetic fly ash, 93 parts of mineral powder, 910 parts of pre-wetted conductive fly ash ceramsite and 745 parts of pre-wetted conductive fly ash ceramic sand and mixing them evenly under mechanical stirring to obtain dry material I;
[0071] S4, 165 parts of water minus the water absorption of conductive fly ash ceramsite and conductive fly ash ceramic sand and 50 parts of water used for carbon fiber to obtain the remaining water, take 5 parts of water reducer, pour it into the remaining water and stir evenly, then add it to the dry material I and mix and stir evenly to obtain slurry J;
[0072] S5. Add the ultrasonically dispersed carbon fiber mixture K into the slurry J, and stir evenly to obtain the structural and functional integrated conductive concrete.
[0073] Comparative Example 1
[0074] A conductive concrete with integrated structure and function comprises, by weight ratio, 215 parts of cement, 62 parts of low-magnetic fly ash, 93 parts of mineral powder, 910 parts of conductive fly ash ceramsite, 745 parts of conductive fly ash ceramic sand, 5 parts of high-performance polycarboxylic acid water reducer, and 165 parts of water. The low-magnetic fly ash, conductive fly ash ceramsite and conductive fly ash ceramic sand are prepared by the method of the above embodiment 1.
[0075] When preparing the above concrete, the following steps are included:
[0076] S1. Take 910 parts of conductive fly ash ceramsite and 745 parts of conductive fly ash sand in proportion by mass and soak them in water for 24 hours respectively, and weigh them to determine the water absorption of the conductive fly ash ceramsite and the conductive fly ash sand;
[0077] S2, taking 215 parts of cement, 62 parts of low magnetic fly ash, 93 parts of mineral powder, 910 parts of pre-wetted conductive fly ash ceramsite and 745 parts of pre-wetted conductive fly ash ceramic sand and mixing them evenly under mechanical stirring to obtain dry material I;
[0078] S3. The remaining water is obtained by subtracting the water absorption of the conductive fly ash ceramsite and the conductive fly ash ceramic sand from 165 parts of water. 5 parts of water reducer are poured into the remaining water and stirred evenly. The mixture is then added to the dry material I and mixed evenly to obtain a conductive concrete with integrated structure and function.
[0079] Comparative Example 2
[0080] A conductive concrete with integrated structure and function, comprising, by weight ratio: 215 parts of cement, 62 parts of low magnetic fly ash, 93 parts of mineral powder, 1020 parts of common coarse aggregate, 800 parts of common fine aggregate, 1 part of carbon fiber, 5 parts of high performance polycarboxylate water reducer, 165 parts of water, and the low magnetic fly ash is prepared by the method of the above embodiment 1. The carbon fiber is polyacrylonitrile-based carbon fiber with a length of 5 to 8 mm, a diameter of 6 to 8 μm, and a density of 1.5 to 2 g / cm 3 , tensile strength is 4-8GPa, tensile modulus is 300-500GPa, carbon content is>90%. Ordinary coarse aggregates are crushed stone and pebbles, and ordinary fine aggregates are river sand.
[0081] When preparing the above concrete, the following steps are included:
[0082] S1. According to the mass ratio, 1 part of carbon fiber is added to 50 parts of water and ultrasonically dispersed for 30 minutes to obtain an ultrasonically dispersed carbon fiber mixed solution K for standby use;
[0083] S2, take 215 parts of cement, 62 parts of low magnetic fly ash, 93 parts of mineral powder, 1020 parts of common coarse aggregate, and 800 parts of common fine aggregate and mix them evenly under mechanical stirring to obtain dry material I;
[0084] S3, take 5 parts of water reducer, pour it into the remaining 115 parts of water, stir evenly, add it into dry material I, mix and stir evenly, and obtain slurry J;
[0085] S4. Add the ultrasonically dispersed carbon fiber mixture K into the slurry J, and stir evenly to obtain the structural and functional integrated conductive concrete.
[0086] Comparative Example 3
[0087] A conductive concrete with integrated structure and function, comprising, by weight ratio: 215 parts of cement, 62 parts of low magnetic fly ash, 93 parts of mineral powder, 1020 parts of common coarse aggregate, 800 parts of common fine aggregate, 5 parts of high-performance polycarboxylate water reducer, 2.5 parts of carbon fiber, 165 parts of water, and the low magnetic fly ash is prepared by the method of the above embodiment 1. The carbon fiber is polyacrylonitrile-based carbon fiber with a length of 5 to 8 mm, a diameter of 6 to 8 μm, and a density of 1.5 to 2 g / cm 3 , tensile strength is 4-8GPa, tensile modulus is 300-500GPa, carbon content is>90%. Ordinary coarse aggregates are crushed stone and pebbles, and ordinary fine aggregates are river sand.
[0088] When preparing the above concrete, the following steps are included:
[0089] S1. Take 2.5 parts of carbon fiber in 50 parts of water and ultrasonically disperse them for 30 minutes to obtain an ultrasonically dispersed carbon fiber mixed solution K for later use;
[0090] S2, take 215 parts of cement, 62 parts of low magnetic fly ash, 93 parts of mineral powder, 1020 parts of common coarse aggregate, and 800 parts of common fine aggregate and mix them evenly under mechanical stirring to obtain dry material I;
[0091] S3, take 5 parts of water reducer, pour it into the remaining 115 parts of water, stir evenly, add it into dry material I, mix and stir evenly, and obtain slurry J;
[0092] S4. Add the ultrasonically dispersed carbon fiber mixture K into the slurry J, and stir evenly to obtain the structural and functional integrated conductive concrete.
[0093] Test method:
[0094] The compressive strength and electrical conductivity of the concrete of Example 2 and Comparative Examples 1 to 3 were tested, and the test results are shown in the following table:
[0095] Test items Compressive strength(MPa) Conductivity (S / m) Example 2 40.7 0.01 Comparative Example 1 41.6 0.005 Comparative Example 2 36.2 0.003 Comparative Example 3 34.8 0.003
[0096] It can be concluded from the above table that the compressive strength and electrical conductivity of the structural and functional integrated conductive concrete prepared in Example 2 are significantly better than those of Comparative Examples 1 to 3:
[0097] From the performance difference between Example 2 and Comparative Example 1, it can be seen that when conductive ceramsite is added, only a small amount of carbon fiber can greatly improve the conductivity of concrete;
[0098] From the performance difference between Example 2 and Comparative Example 2, it can be seen that after adding conductive ceramsite, the concrete forms a complete conductive network, so the conductive performance is excellent, and the addition of conductive ceramsite as aggregate does not reduce the compressive strength of the concrete;
[0099] From the performance difference between Comparative Example 2 and Comparative Example 3, it can be seen that if conductive ceramsite is not added but ordinary aggregate is added, concrete cannot form a complete conductive network, and even if the amount of carbon fiber added is increased, a better conductive effect cannot be obtained.
[0100] It should be noted that in this application, the letters in calcined fly ash A, calcined fly ash solution B, wet high magnetic fly ash C, low magnetic fly ash solution D, fly ash ceramsite raw balls E, crude conductive fly ash ceramsite F, dry material I, slurry J and ultrasonically dispersed carbon fiber mixture K have no special limiting meaning and are only used to distinguish substances and materials.
[0101] This embodiment is only a further explanation of the present invention, not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to this embodiment as needed, but as long as it is within the scope of the claims of the present invention, it will be protected by the patent law.
Claims
1. A method for preparing conductive fly ash ceramsite, characterized in that: include: S1. placing high iron fly ash containing magnetite and hematite in a roasting furnace, and roasting at a roasting temperature of 800° C. for 30 min to obtain roasted fly ash A, wherein the roasted fly ash A contains magnetite; S2, dispersing the calcined fly ash A in water to obtain a calcined fly ash solution B, separating the magnetic substance in the calcined fly ash solution B to obtain wet high magnetic fly ash C and low magnetic fly ash solution D; S3, drying the wet high magnetic fly ash C to constant weight to obtain high magnetic fly ash; drying the low magnetic fly ash solution D to constant weight to obtain low magnetic fly ash; S4, granulating the high magnetic fly ash to form fly ash ceramsite raw balls E; S5, calcining the fly ash ceramsite raw balls E in a reducing atmosphere, including three stages: In the first stage, the preheating temperature is 400°C and the preheating time is 30 minutes; In the second stage, the calcination temperature was 1100°C and the sintering time was 20 min; In the third stage, rapid cooling for 15 min, the temperature dropped to room temperature, and crude conductive fly ash ceramsite F was obtained; S6. Screening the crude conductive fly ash ceramsite F to obtain conductive fly ash ceramsite and conductive fly ash ceramic sand, wherein the particle size of the conductive fly ash ceramsite is ≥5 mm and ≤20 mm, and the particle size of the conductive fly ash ceramic sand is ≥1.25 mm and <5 mm.
2. The method for preparing conductive fly ash ceramsite according to claim 1, characterized in that: The high iron fly ash has a Fe2O3 content of 14% to 20%, a SiO2 content of 45% to 54%, an Al2O3 content of 25% to 30%, a Na2O content of 0.5% to 1%, a K2O content of 0.5% to 1%, a CaO content of 1% to 4%, a MgO content of 0.5% to 3%, and a residual carbon content of 4% to 6%.
3. The method for preparing conductive fly ash ceramsite according to claim 1, characterized in that: The mass ratio of the calcined fly ash A to water is 1:9 to 1:
4.
4. The method for preparing conductive fly ash ceramsite according to claim 1, characterized in that: The content of Fe2O3 in the high magnetic fly ash is 45% to 60%, and the content of Fe2O3 in the low magnetic fly ash is 2% to 6%.
5. The method for preparing conductive fly ash ceramsite according to claim 1, characterized in that: The apparent density of the conductive fly ash ceramsite is 2200-2500 kg / m 3 , the cylinder pressure strength is 8~12MPa.
6. The method for preparing conductive fly ash ceramsite according to claim 1, characterized in that: The apparent density of the conductive fly ash ceramic sand is 2350-2600 kg / m 3 , the cylinder pressure strength is 9~12MPa.
7. The method for preparing conductive fly ash ceramsite according to claim 1, characterized in that: The step S2 includes: Step S21, stirring the roasted fly ash solution B by a magnetic bar with a magnetic induction intensity of 1T, so that the magnetic substance in the roasted fly ash solution B is adsorbed on the surface of the magnetic bar, and the magnetic substance on the surface of the magnetic bar is collected for later use; repeating the above process until the surface of the magnetic bar with a magnetic induction intensity of 1T is no longer adsorbed with magnetic substances; Step S22, stirring the roasted fly ash solution B after the treatment in the above step S21 by a magnetic bar with a magnetic induction intensity of 1.2T, so that the magnetic substance in the roasted fly ash solution B is adsorbed on the surface of the magnetic bar with a magnetic induction intensity of 1.2T, collecting the magnetic substance on the surface of the magnetic bar with a magnetic induction intensity of 1.2T for later use, and repeating the operation until the surface of the magnetic bar with a magnetic induction intensity of 1.2T is no longer adsorbed with magnetic substances; Step S23, the collected magnetic substances are mixed to obtain wet high magnetic fly ash C, and the roasted fly ash solution B is processed in step S22 to obtain low magnetic fly ash solution D.
8. A conductive concrete with integrated structure and function, characterized in that: The composition comprises, by mass ratio, 200 to 220 parts of cement, 60 to 70 parts of low magnetic fly ash, 90 to 100 parts of mineral powder, 880 to 930 parts of conductive fly ash ceramsite, 720 to 760 parts of conductive fly ash ceramic sand, 0.5 to 2 parts of carbon fiber, 4 to 6 parts of water reducing agent, and 165 to 170 parts of water. The low magnetic fly ash, conductive fly ash ceramsite and conductive fly ash ceramic sand are prepared by the method described in any one of claims 1 to 7.
9. The conductive concrete with integrated structure and function according to claim 8, characterized in that: The carbon fiber is a polyacrylonitrile-based carbon fiber with a length of 5 to 8 mm, a diameter of 6 to 8 μm, and a density of 1.5 to 2 g / cm 3 , tensile strength is 4-8GPa, tensile modulus is 300-500GPa, and carbon content is >90%.
10. The conductive concrete with integrated structure and function according to claim 8, characterized in that: The water reducer is a high-performance polycarboxylate water reducer.
11. A method for preparing structurally integrated conductive concrete as claimed in claim 8, characterized in that: The method includes: S1. Take 880-930 parts of conductive fly ash ceramsite and 720-760 parts of conductive fly ash ceramic sand according to the mass ratio, soak them in water for 24 hours respectively, and weigh them to determine the water absorption of the conductive fly ash ceramsite and the conductive fly ash ceramic sand; S2, taking 0.5-2 parts of carbon fiber and dispersing them ultrasonically in 40-60 parts of water for 30-60 minutes to obtain an ultrasonically dispersed carbon fiber mixed solution K for standby use; S3, taking 200-220 parts of cement, 60-70 parts of low magnetic fly ash, 90-100 parts of mineral powder, 880-930 parts of pre-wetted conductive fly ash ceramsite and 720-760 parts of pre-wetted conductive fly ash ceramic sand, stirring and mixing them evenly to obtain dry material I; S4, take 4 to 6 parts of water reducing agent, pour it into the remaining water and stir it evenly, then add it into the dry material I and mix and stir evenly to obtain slurry J; S5. Add the ultrasonically dispersed carbon fiber mixture K into the slurry J, and stir evenly to obtain the structural and functional integrated conductive concrete.
Citation Information
Patent Citations
Iron tailing large-slump high-strength conductive concrete and preparation method thereof
CN112521076A
High iron pulverized ash cement-based composite wave-absorbing material applied to buildings and preparation method thereof
CN101525224A
Synthesis method of magnetic porous ceramsite based on pulverized coal ash magnetic bead
CN104772106A
Preparation method of conductive material and conductive material
CN108117365A
Conductive ceramsite filler for bio-trickling filter and preparation method of conductive ceramsite filler
CN113264772A